2015
DOI: 10.1590/1414-462x201500040055
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização do consumo alimentar de adultos por meio de questionário simplificado: contribuição para os estudos de vigilância alimentar e nutricional

Abstract: Resumo Objetivo Avaliar se questões marcadoras de hábitos alimentares podem caracterizar o consumo habitual de forma satisfatória. Métodos Foram obtidas informações sobre o consumo alimentar utilizando dois métodos: três dias não consecutivos de recordatório de 24 horas (R24h) e um questionário sobre hábitos alimentares (QHA). A concordância entre os dados categóricos de consumo alimentar foi testada pela comparação de fontes de informações independentes referida no QHA e R24h categorizado, sendo medida pelo c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
0
4
0
7
Order By: Relevance
“…Using single components of the diet, such as percent of calories from fat or specific nutrients intake, can lead to misclassifications of overall diet quality [28,29]. Research has shown that using shorter questionnaires that target key diet components to generally analyze diet quality (instead of considering the intake of each nutrient alone) may be a more feasible and representative way to evaluate diet quality of a population under study [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Using single components of the diet, such as percent of calories from fat or specific nutrients intake, can lead to misclassifications of overall diet quality [28,29]. Research has shown that using shorter questionnaires that target key diet components to generally analyze diet quality (instead of considering the intake of each nutrient alone) may be a more feasible and representative way to evaluate diet quality of a population under study [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, they were submitted to a nutritional assessment through a usual dietary recall, 13 for control and normalization of diet during the training period.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 They are not very practical instruments for situations in which contact between health professionals and their patients is brief. The importance of proposing a question about self-perception, capable of identifying people's eating habits 4,9 and the risk represented by unhealthy eating habits, should be reflected in the indication of target groups for possible interventions. 10 The objective of this article was to analyze the prevalence of positive self-perception of diet and its association with sociodemographic and behavioral factors, morbidities, self-perception of health/weight and body weight care in the municipality of Rio Grande, located in Rio Grande do Sul state, Brazil, in 2016.…”
Section: Introductionmentioning
confidence: 99%